Prevalencia de hiperplasia epitelial focal en escolares de la comuinidad indígena de crisantia, Municipio de Jardín, Antioquia, 1998. - Gustavo Matute-T; Leonor Victoria González-P; Edwin Acosta-O; Mónica Restrepo-V (Universidad de Antioquia, 1999)
This study was developed during the second semester of 1998 in the indigenous communiyi-Ernbera Chaim'of Cristiania, ciO7offardin, at the southwest of Antioquia. In the search for Focal Epitelial Hyperplasia, 200 school children between 4 and 14 years old were examined, finding a 7.5 per cent prevalence. The age of the patients varied between 5 and 9 years in the 46.6 per cent of the 15 cases found and there was no significative sex difference. There was found some degree of consanguiniz and familiar occurrence of the disease in the 33% of patients. In the 66.6% of the cases the lesions were initially located in the lower lips and yugalrnucous. The number of lesions was incremented in the 66.6% and its size irt the 46.6%. Clinically, the analyzed lesions were sessile, had well delineated borders, and showed no symptoms in 80% of patients. 20.7% of these lesions were ubicated on the yugal mucous and its size oscillated between Sand 8 mm. Histologically, the.findings were characterized by epithelial acantosis, hjperkeratosis, papilornatosis, basal cells hypetplasia and presence of koilocytes in the upper layers; these changes varied _from mild to moderated and the severe form was present in fewer proportion. 13.3% of the cases were PVH positive by- inmunohistochernistry techniques while 100% were neg-ative by PO? and in situ hybridization for serotypes 6, 11, 16 and 18